Youth as Actors in Peace and Human Rights Education (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Speaking of violence, youth are often perceived as perpetrators of violence3 and are therefore seen as the perfect target group for peace and human rights education projects. However, more recently, voices from the field and from academia, highlight that “peace and conflict research has insufficiently considered youth as relevant actors in [development and] peacebuilding processes” (Del Felice & Wissler 2007: 4; Fischer 2004). Therefore, as is stated in the European Charter on the Participation of  Young People in Local and Regional Life, youth should be given “the rights, the means, the space, the opportunities for participation in decision-making and for influencing decision-making processes, […] and active involvement in activities that contribute to the positive forming of society”. In line with this, the youth mid-term report on the UN Decade for a Culture of Peace and Non-violence for the Children of the World from 2006 voices the wish of youth to be more involved in decision-making processes.